From Einstein to Infinity: Understanding the Complex Relationship between Velocity and Mass - Ali Mohamad Khalife (Fundamental Research and Application of Physical Science Vol. 8, 2023)
The purpose of this theory is to explore and elucidate the phenomena that Einstein predicted in 1905, which proposes that the mass of an object increases with its velocity or speed. In classical physics, an object gains energy of motion, but in relativity, this kinetic energy manifests as extra mass. As an object approaches the speed of light, its mass theoretically becomes "infinite," though the concept of infinite mass remains a topic about which little is known. This paper will delve into the reasons and mechanisms behind these phenomena, while also touching upon the subject of antimatter. Recent discoveries have shown that antimatter is present in the cosmos, and when a particle encounters its antiparticle, both annihilate each other, releasing radiant energy as predicted by Einstein’s famous equation, E=mc².